2023
DOI: 10.1038/s42003-023-05341-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics reveal neuroprotection of Acer truncatum Bunge Seed extract on hypoxic-ischemia encephalopathy rats under high-altitude

Xianyang Chen,
Yige Song,
Wangting Song
et al.

Abstract: Hypoxic-ischemic encephalopathy (HIE) at high-altitudes leads to neonatal mortality and long-term neurological complications without effective treatment. Acer truncatum Bunge Seed extract (ASO) is reported to have effect on cognitive improvement, but its molecular mechanisms on HIE are unclear. In this study, ASO administration contributed to reduced neuronal cell edema and improved motor ability in HIE rats at a simulated 4500-meter altitude. Transcriptomics and WGCNA analysis showed genes associated with lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
0
3
1
Order By: Relevance
“…Conversely, some studies indicate that C24:1 has contributed to brain growth and cognition [20,21,51]. In our study, we observed a signi cant decrease in Cer24:1 and FA24:1 in the LA group.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Conversely, some studies indicate that C24:1 has contributed to brain growth and cognition [20,21,51]. In our study, we observed a signi cant decrease in Cer24:1 and FA24:1 in the LA group.…”
Section: Discussioncontrasting
confidence: 59%
“…In addition, fatty acids associated with neuronal membrane integrity and function are important for brain hypoperfusion [19]. Our previous study also suggest the effects of nervonic acid (FA 24:1) on neuroprotection of rats suffered by hypoxic-ischemia encephalopathy [20,21]. A study including 794 000 non-overlapping people and 34817 cerebrovascular outcomes proves that level of long chain omega 3 fatty acids is inverse association with cerebrovascular risk [22].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, despite these precautions, subtle variations in pre-analytical procedures could still potentially impact the results. Moreover, analysis was limited by a small sample size, preventing advanced statistical techniques such as ternary plots or logistic regression [ 110 ]. It is important to validate these findings and undertake more comprehensive analyses with larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%